Influence of Synthesis on Constitution and Gas Sensing Property of SnO2 Nanomaterial - Mu, Xiaoming; Peng, Chuanyun; Wu, Chunlai (Asian Journal of Chemistry, 2011)
In this paper, nanostructure SnO2 was prepared by dissolving tin granule in citric acid and gaining the precursor, which was treated with different ways and calcinated. The influence of treatment with the precursor on the gas sensing property of SnO2 was studied. The precursor was treated with different methods and calcined at different temperature. SnO-doping SnO2 was prepared from annealing the washed precursor and pure SnO2 was synthesized from annealing the unwashed precursor. Four nanomaterials were obtained. The phases, constitution, morphology of them were characterized by XRD and SEM. Gas sensors were fabricated and an investigation into the SnO2-based gas-sensing properties has been conducted. Compared to SnO-doping SnO2, pure SnO2 sensor shows much better gas sensing properties. It is more sensitive to H2S, Cl2, C2H5OH and HCHO than SnO-doping SnO2.